The Green Frog and Desalination: A Nyungar Metaphor for the (Mis-) Management of Water Resources, Swan Coastal Plain, Western Australia - McDonald, E.; Coldrick, B.; Christensen, William (Oceania Publications, 2008)
This article outlines the key findings of a study commissioned by the Western Australian Department of Environment (as of July 1, 2006 the Department of Environment and Conservation) to investigate Aboriginal cultural values associated with groundwater-related environmental features and processes on an aquifer known as the 'Gnangara Mound' in Perth's northern metropolitan region. (1) The traditional owners of this region are part of the wider Nyungar (also spelt Nyoongar) population of south-western Australia (see Baines 1988; Birdsall 1988; Sansom 1983 and Toussaint 1992 for discussion of Nyungar history, identity and culture). The study was part of a broader Government-sponsored program aimed at understanding indigenous values associated with surface and groundwater, and watercourses. The former Water and Rivers Commission, now part of the State's Department of Environment and Conservation, has in recent years commissioned a number of studies addressing indigenous perceptions of water in Western Australia. These studies have typically been wide-ranging explorations of cultural and environmental values contributing to overall water resources planning and management (see, for example, Goode 2003; Toussaint, Sullivan, Yu and Mularty 2001; Toussaint, Sullivan and Yu 2005; Yu 2002). Genuine concern to take Aboriginal perspectives into consideration during water resource planning has been a factor in the Commission's investigations. Two pieces of legislation have been important in giving these investigations shape: Western Australia's Aboriginal Heritage Act 1972 (amended in 1980) and the Federal Government's Native Title Act (1993).In common with Aboriginal groups around Australia, the indigenous people, or Nyungars, of Perth adopt a holistic attitude towards groundwater resources. Of cultural significance are lakes, springs, soaks and watercourses that feature in Dreamtime creation narratives. Perth is experiencing major water shortages and many Nyungars feel that the degradation of the freshwater supply is a result of mismanagement and unsustainable development by non-Aboriginal people. Proposals for dealing with the issue are seen as equally out of balance with the natural order of things. Water regulators have much to learn from indigenous Australians about water and environmental management. Although water continues to be central to Nyungar identity, the study on which this article is based found evidence of attenuated knowledge about the Dreaming, with discontinuities evident in the way significance is increasingly being read in everyplace rather than in specific ‘story places’.